"Anak Manusia” dalam Daniel 7:13 - Robi Prianto; Irwanda (Te Deum (Jurnal Teologi dan Pengembangan Pelayanan), 2025)
The concept of the “Son of Man” in Daniel 7:13 holds deep theological significance and is closely connected to the Christian hope in the second coming of Jesus Christ. This study aims to explore the interpretation and application of this text within the context of Christian theology using a qualitative method with a biblical exegetical approach. The findings reveal that the “Son of Man” is not merely a collective symbol of God’s people but refers to the person of Jesus Christ, who will return in glory to fulfill God’s plan of salvation. This concept enriches eschatological understanding regarding eternal rule, final judgment, and the restoration of creation. The study emphasizes that the “Son of Man” is central to Christian eschatological hope, providing a strong theological foundation for faith in Christ’s return.